Deposition of Super-Hydrophobic Silver Film on Copper Substrate and Evaluation of Its Corrosion Properties - Fani Stergioudi (MDPI AG, 2021)
A simple and versatile chemical solution deposition process is reported to manipulate the wettability properties of copper sheets. The whole process has the advantage of being time-saving low cost and environment-friendly. An adherent silver coating was achieved under optimal conditions. Scanning electron microscopy and X-ray diffraction were used to examine the silver film structure. A confocal microscope was used to record the 3D topography and assess the film roughness of the surface. A dual morphology was revealed, consisting of broad regions with feather-like structured morphologies and some areas with spherical morphologies. Such silver-coated copper samples exhibited a sufficiently stable coating with superhydrophobicity, having a maximum water contact angle of 152°, along with an oleophilic nature. The corrosion behavior of the produced hydrophobic copper under optimal conditions was evaluated by means of potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) using a 3.5% NaCl solution. The corrosion protection mechanism was elucidated by the proposed equivalent circuits, indicating that the superhydrophobic silver coating acted as an effective barrier, separating the Cu substrate from the corrosive solution. The superhydrophobic coating demonstrated enhanced anti-corrosion properties against NaCl aqueous solution in relation to the copper substrate as indicated from both EIS and potentiodynamic polarization experiments.